A Systematic Review of Language Teachers’ Professional Development in Western Indonesia: Current Practices and Challenges - Alridya, Briana Putri (English Language Education, Universitas Internasional Batam, 2025)
Professional development is crucial in improving teachers’ teaching quality and student outcomes. Hence, it is essential to identify the challenges and the current practices that language teachers faced in professional development, in Western Indonesia. To achieve the aim of this study. This study systematically reviews fifteen empirical articles from 2018 to 2025, sourced from SINTA, Google Scholar, and EBSCO. The analysis results were categorized in five themes: (1) teachers’ participating in offline and online workshops, (2) teachers involving in formal and informal training, (3) cultural-discursive arrangements influencing teachers’ participation, (4) material-economic arrangements limiting acccess, and (5) social-political arrangements shaping institutional. The results show that teachers heavily rely on external training, workshops dominate in current practices, and structural barriers such as limited resources and extrinsic motivation limit teachers’ participation. By exploring specific challenges and practices in Western Indonesia and putting them within the Theory of Practice Architecture, the study synthesizes these findings and adds to the literature on professional development in Indonesia. The review emphasizes the necessity of context-specific methods that use school-based models, technology innovation, and mentoring to promote continuous teacher development.